The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1136/bjsports-2022-106687
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of athlete mental health symptoms and disorders: a supplement to the International Olympic Committee’s consensus statement on injury and illness surveillance

Abstract: In 2019, the International Olympic Committee (IOC) published a consensus statement outlining the principles for recording and reporting injury and illness in elite sport. The authors encouraged sport federations to adapt the framework to their sport-specific context. Since this publication, several sports have published extensions to the IOC consensus statement.In response to a paucity of epidemiological data on athlete mental health, the IOC mental health working group adapted the IOC consensus statement on i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…In aggregate, it appears that rates of depression among the young adult general population are higher than among collegiate athletes 3 4 24. Although those who compete in collegiate sports may have lower rates of depression compared with the general population, the absolute rate of mental health issues in this population remain concerning with the NCAA and International Olympic Committee recommending regular mental health screening in athletes 5–8…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In aggregate, it appears that rates of depression among the young adult general population are higher than among collegiate athletes 3 4 24. Although those who compete in collegiate sports may have lower rates of depression compared with the general population, the absolute rate of mental health issues in this population remain concerning with the NCAA and International Olympic Committee recommending regular mental health screening in athletes 5–8…”
Section: Discussionmentioning
confidence: 99%
“…In the USA, suicide rates across all ages increased by approximately 36% between 2001 and 2021 2. Data from 2001 to 2020 demonstrate suicide rates, specifically among young adults,3–9 have also increased, rising to their highest level in 2020 10. Death by suicide is now the third leading cause of death in the USA in the general population ages 18–24 after accidents and homicide 10.…”
Section: Introductionmentioning
confidence: 99%
“…Although future surveillance work will incorporate the most contemporary diagnostic codes, the current study is limited in terms of classifying infectious illnesses as their own body system (‘infections’), whereby more recent versions of the Orchard Sports Injury and Illness Classification System (OSIICS) system would include infection as an aetiology within other body system categories. Lastly, out of concerns regarding athlete privacy and the abstention from delivering formal psychological diagnoses, along with the absence of standardised methods for monitoring mental health conditions among athletes during the data collection phase (the mental health supplement to the IOC surveillance consensus statement was published in July 202347), the sports medicine and psychological services team made the decision not to classify mental health interactions, consequently omitting them from the overarching surveillance programme. As such, a broad aspect of holistic athlete health and well-being remains unaddressed in the current framework, and thus it is imperative that future athlete health surveillance systems take this into account, as has been recently recommended 47…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, out of concerns regarding athlete privacy and the abstention from delivering formal psychological diagnoses, along with the absence of standardised methods for monitoring mental health conditions among athletes during the data collection phase (the mental health supplement to the IOC surveillance consensus statement was published in July 202347), the sports medicine and psychological services team made the decision not to classify mental health interactions, consequently omitting them from the overarching surveillance programme. As such, a broad aspect of holistic athlete health and well-being remains unaddressed in the current framework, and thus it is imperative that future athlete health surveillance systems take this into account, as has been recently recommended 47…”
Section: Discussionmentioning
confidence: 99%
“…Then, in order to prevent any misuse of the information for purposes such as athlete selection or contract negotiations, it is important to strictly and reliably implement informed consent for athletes and the de-identification of personal information. Mountjoy et al [44] have recently developed surveillance formats that may be useful in reviewing diagnosis, treatment and outcomes and in developing practice guidelines for athletes. With regards the mental health of elite athletes, Reardon et al [45] identified 13 key steps for future directions.…”
Section: The Role Of Psychiatrists In Researchmentioning
confidence: 99%